PENGEMBANGAN KERAJINAN MAINAN ANAK DESA JIKEN, TULANAGAN, SIDOARJO DALAM MENINGKATKAN KAPASITAS PRODUKSI - Suprayitno, Eko Agus; Hindarto, -; Evianti, Ade (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
Jiken village located in the district Reinforcement, Sidoarjo regency, ±10 km from downtown Sidoarjo. Jiken village is a village of SMEs engaged inthe activities of Household Appliance Craftsmen, Artisans Batik, EmbroideryCraftsmen, Artisans Bags and Aquaculture in ponds. The rest of the villagersJiken many craftsmen who work as children's toys. In this dedication programraised issues 2 Partners, which Partner 1 and Partner 2, both the partners workas artisans craft toys. Crafts Toys effort is capable of producing 48 scores for 2weeks, scores of 3.4 per day. Development of a toy Kids Crafts Village JikenTulanagan Kab. Sidoarjo in increasing production capacity through science andtechnology program for Community (IbM) Partner 1 and Partner 2 is going welland according to plan. Several problems Partner 1 (Artisans Children toys) andPartner 2 (Craftsmen toys Children) has been given a solution according to planand the process runs smoothly solutions which include among others: 1). Assistthe process of production, particularly in providing assistance Making canscutting tools, to be able to do the cutting fast and qualified cans (canned chunksresults have pieces of the same pattern). As well as providing aid Pengeplongzinc/tin to increase the production capacity of zinc perforation ready assembledinto a tool toys are ready for use. Then conduct training on cutting tools andpengeplong pengoprasian zinc/tin. Results of this aid shown to increase theproduction capacity of up to 3-fold. Namely the production capacity of 1920products every 28 days, increasing to 5760 products every 28 days. 2). Providetraining on procedures for preparing the financial statements properly andaccording to the rules - the rules so that banks can use to access funding frombanks and analyzes the development of the business. 3). Assist in obtaining alicense for the product brand logo to enhance the competitiveness of products and the level of consumer confidence in the product. Logo and realize products that are legal in toys Child Craft Tool Partner 1 and Partner 2. Logo that carried the "Bintang Tiga Jaya"